Two Approaches to School Counseling as a Profession: From Boundaries to Core - Rubin, Osnat (Professions and professionalism, 2024)
The literature on school counseling as a profession has emphasized the classic boundaries approach, which perceives the profession's jurisdiction as a product of a power struggle for a distinct uniqueness. This paper aims to provide an alternative approach, in line with current approaches to professions. The author establishes a core-characteristics approach, highlighting the profession's core character as its source of legitimacy, encouraging continuous education and adapting to dynamic contexts. This mixed-methods study investigated the perceptions of school counselors and teachers regarding the status and sources of the counselor's legitimacy. The findings show that school counselors were recognized as influential professionals, and their main source of legitimacy was deemed to be character attributes, more than knowledge and education. Differences in perceptions were found vis-à-vis the profession's multi-specialist contexts. Further examining the core characteristics of the profession may enhance its legitimacy and help it thrive.